Implementasi modul purchase pada UMKM berbasis Odoo ERP - Yuli Fatmilia (Department of Accounting Universitas PGRI Yogyakarta, 2024)
Competition among small and medium-sized enterprises is intensifying across all sectors, prompting business innovation to increase market share. Many SME business processes remain manual and encounter various operational obstacles. To reduce problems and increase efficiency, they need to implement an accounting system. ERP Oddo is a solution that SMEs can use to integrate all company data into business processes. Implementing ERP Oddo aims to increase the efficiency and effectiveness of the purchasing process, which the system has not yet integrated. This research employs a descriptive qualitative method, with the subject being the Point of Sale (PoS) in the purchase module. This study uses interview techniques and direct observation of survey respondents. The primary data are obtained through interviews with the owner, and the secondary data are obtained through literature studies related to the research object. The results of this study indicate that implementing the Odoo ERP system is an appropriate step to enhance business efficiency.